Cyprus and the politics of memory (London)
vii, 275 sayfa
Keywords: “The island of Cyprus has been bitterly divided for more than four decades. One of the most divisive elements of the Cyprus conflict is the writing of its history, a history called on by both communities to justify and explain their own notions of justice. While for Greek Cypriots the history of Cyprus begins with ancient Greece, for the Turkish Cypriot community the history of the island begins with the Ottoman conquest of 1571. The singular narratives both sides often employ to tell the story of the island are, as this volume argues, a means of continuing the battle which has torn the island apart, and an obstacle to resolution. Cyprus and the Politics of Memory re-orientates history-writing on Cyprus from a tool of division to a form of dialogue, and explores a way forward for the future of conflict resolution in the region“ --